Effects of Estrogens on Central Nervous System Neurotransmission: Implications for Sex Differences in Mental Disorders - Krolick, Kristen N. (Prog Mol Biol Transl Sci, 2018)
Nearly one of every five US individuals aged twelve years old or older live with certain types of mental disorders. Men are more likely to use various types of substances, while women tend to be more susceptible to mood disorders, addiction, and eating disorders, all of which are risks associated with suicidal attempts. Fundamental sex differences exist in multiple aspects of functions and activities of neurotransmitter-mediated neural circuits in the central nervous system (CNS). Dysregulation of these neural circuits would lead to various types of mental disorders. The potential mechanisms of sex differences in the CNS neural circuitry regulating mood, reward, and motivation are only beginning to be understood, although they have been largely attributed to the effects of sex hormones on CNS neurotransmission pathways. Understanding this topic is important for developing prevention and treatment of mental disorders that should be tailored differently between men and women. Studies using animal models have provided important insights into pathogenesis, mechanisms, and new therapeutic approaches of human diseases, but some concerns remain to be addressed. The purpose of this chapter is to integrate human and animal studies involving the effects of sex hormone estrogens on CNS neurotransmission, reward processing, and associated mental disorders. We provide an overview of existing evidence for the physiological, behavioral, cellular and molecular actions of estrogens in the context of controlling neurotransmission in the CNS circuits regulating mood, reward and motivation, and discuss related pathology that leads to related mental disorders.